Historical Stained Glass Painting Techniques Technology and preservation - Machado, Andreia Sofia Simões Gouveia (2019)
The aim of this project is the study of the painting techniques applied on stained glass, namely blue enamels, sanguine red and grisaille. The research and interpretation of several historical treatises dated to between the 12th and the 18th centuries was performed, with a study of the production technology of the selected painting techniques, from the preparation of the pigment to the preparation of the paint. With this in mind, selected raw materials used in the productions of blue enamels were characterized, followed by the reproduction of selected historical recipes of blue enamels, sanguine red and grisaille. Parameters such as firing temperature, grinding and binding agents used to apply the paint on glass were considered. The methodology selected was based on the chemical and morphological characterization of both reproduced powder and paint samples by means of a multi-analytical approach. In addition to the reproduction of the selected painting techniques, corrosion studies of blue enamel powder and paint samples were performed in order to provide new insights on the corrosions mechanisms involved. The results obtained were compared with selected painted stained-glass fragments from Portuguese collections, mainly the ones located in Batalha Monastery, Charola from Convento de Cristo in Tomar and Pena National Palace in Sintra. The present study concluded that the choice of the raw materials to the production of the paint, the binder used to apply the paint, and parameters such as firing temperature and heating rate, had an impact on the outcome, resulting on a better adhesion of the paint layer to the base glass. The use of zaffer as a colouring agent does not allow determination of the outcome of the paint, while adding powdered glass such as smalt gives to the glass painter the opportunity to know the final result before firing. As for sanguine red paint, it is concluded that the final outcome of the paint is strongly influenced by the heating rate. In addition, the use of gum arabic as a binder, or in the pigment itself, provides a better adhesion of the paint layer to the base glass. Regarding the grisaille painting, the main differences between the recipes lay on the composition of the lead-based glass and on the ratios between this and the colouring agents. Furthermore, it was also possible to conclude that there is an evolution of the morphology of the grisailles towards a higher homogeneity of the surface. The corrosion studies performed on blue enamels allowed to conclude that with the lixiviation of the alkaline components of the enamel, cobalt will be influenced by other neighbouring ions, leading to a change of colour. In some cases, Pb2+ ions may also be the responsible for this colour change, with the formation of lead white. The results obtained were in a good agreement with the characterization of the selected case studies, evidencing the importance of the intersection between the written sources and the laboratory work.